Detection of time variable gravity signals using terrestrial clock networks ... - Vincent, Asha; Müller, Jürgen (Amsterdam [u.a.] : Elsevier Science, 2023)
The relativistic redshift between two earth-bound clocks can be interpreted in terms of gravity potential variation between the clock locations. A clock with a fractional frequency uncertainty of 10-18 is sensitive to a gravity potential variation of 0.1 m2/s2 or a height difference of 1 cm. Case studies for four regions affected by different mass change processes - Himalaya, Amazon, Greenland, and Fennoscandia - have been carried out. As the clocks rest on the deformable Earth's surface, clock observations do not only include potential variations due to mass changes but also associated variations due to the vertical deformation of the land. For the simulations, vertical displacements were derived from real GNSS (Global Navigation Satellite Systems) measurements, and mass variations were computed from GRACE (Gravity Recovery And Climate Experiment) solutions. In the Himalayan region, seasonal variations with a maximum range of -0.20.2 m2/s2 were obtained. There, early and long-lasting precipitation patterns ...